Dion Boucicault the vampire, the phantom - Boucicault, Dion 1820-1890 (University of Wales Press, 2024)
Almost fifty years before Bram Stoker penned Dracula, Dion Boucicault staged The Vampire, a three-act play that thrilled London audiences as well as Queen Victoria. The production boasted innovations of stagecraft and dramatic composition, to say nothing of the mesmerising performance of Boucicault as the titular creature. After The Vampire closed, Boucicault moved to the United States and revised his play, staging a two-act version renamed The Phantom in 1856. The Vampire has languished in relative obscurity, with no published edition nor critical commentary, since the mid-nineteenth century years. Boucicault’s original handwritten script provides the basis for this first full edition of his innovative tour de force. Similarly, a manuscript of The Phantom, updated by Boucicault for an 1873 production, offers audiences a new version of this influential play. The Vampire and The Phantom can now take their proper place in the lineage of vampire literature that began with Polidori and continues to this day.
Aus dem Inhaltsverzeichnis: "The Vampire (1852), The Phantom (1873)"